Етнічні мотиви в архітектурі сучасних інтер’єрів підприємств харчування - Громнюк, Адріана Ігорівна (Національний університет "Львівська політехніка", 2016)
Дисертацію присвячено розробленню наукових положень використання етнічних мотивів в архітектурі сучасних інтер’єрів підприємств харчування. Визначено засоби та методи застосування етнічних мотивів у предметно-просторовому середовищі цих закладів. Сформовано основні принципи проектування архітектури сучасних інтер’єрів підприємств харчування на основі використання етнічних мотивів, зокрема: вибірковості, образності, цілісності, впізнаваності. Доповнено основні підходи до проектування архітектурного середовища підприємств харчування із застосуванням етнічних мотивів. Розроблено комплексні рекомендації для використання етнічних мотивів різних архітектурно-етнографічних регіонів України в архітектурі інтер’єрів підприємств харчування. Виявлено основні риси цього підходу. Сформовано алгоритм застосування етнічних мотивів в архітектурному проектуванні інтер’єрів сучасних закладів харчування. Диссертация посвящена разработке научных положений использования этнических мотивов в архитектуре современных интерьеров предприятий питания. Определены средства и методы применения этнических мотивов в предметно-пространственной среде этих учреждений. Сформированы основные принципы проектирования архитектуры современных интерьеров предприятий питания на основе использования этнических мотивов, в частности: избирательности, образности, целостности, узнаваемости. Дополнены основные подходы к проектированию архитектурной среды предприятий питания с применением этнических мотивов. Разработаны комплексные рекомендации для использования этнических мотивов различных архитектурно-этнографических регионов Украины в архитектуре интерьеров предприятий питания. Выявлены основные черты этого подхода. Сформирован алгоритм применения этнических мотивов в архитектурном проектировании интерьеров современных предприятий питания. The scholarly thesis is dedicated to development of scientific statements of utilizing the ethnic motives in the architecture of modern interior design in the catering industry. The application of the traditions of ethnic motives in the architecture of Ukrainian interiors in different time periods was discovered and analyzed. The compositional analysis of interiors in the catering industry was performed, which contains the ethnic motives, stylistic and static analysis of modern restaurants. The basic approaches to projecting the architectural environment of catering industry were supplemented by using the ethnic motives among which were approaches of anthropocentrism, individualism, adhocism, mentality, humanization, traditionalism, revivalism, ornamentalism, eclecticism, interactionism, adaptation, optimality, ecology and harmony The instruments of ethic motives usage in object-spatial environment in the catering industry were defined; architectural details that are inherent to the folk architecture, peculiar to compositional structure, traditional local materials; folk furniture with national and regional features; coloristic; the items of decorative and folk art; decorating features of greater details, interior elements; texture and structure of coating materials; ornaments, illumination the elements of nature and greenery; landscaping and natural areas, a corporate identity and its elements. The basic methods of using ethnic motives in the interior architecture in catering industry were developed: styling; direct reproduction; authenticity; styling synthesis with implementation of modern and authentic elements in interior design. The main principles of of projecting of the architecture of modern interiors of catering industry on the basis of ethnic motive usage were formulated, specifically: selectivity (is based on the selection of national, regional or local stylistic interior solution and application of the relevant architectural and artistic instruments; imagery (forecasts the choice of the specific methods in visual solution, displaying ethnic motives in designing the architectural interiors); integrity (which is based on the holistic recreation of the ethnic motives in the artistic image of the architecture of the building, its interiors and elements); recognition (is based on the creation of artistic and imaginative expression of the interior, its stylistic awareness, which is achieved by choice of leading artistic and decorative techniques (relevant for the specific region) and architectural tools. The comprehensive guidelines for the implementation of the ethnic motives of diverse architectural and ethnographic regions of Ukraine (Polissya, Podillya, Hutsulschyna, Boikivschyna, Zakarpatya, Bukovyna, the South of Ukraine, The Middle Nadniprjanschyna, Poltava region and Slobozhanshchyna) in the food business environment were developed. They are based on the architectural and artistic features of the folk architecture in those listed regions and are related to the external housing, the specifics of its architectural and structural elements, their decoration; their interior, furniture and equipment, their ornamentation; decorative elements. Features characterizing the approach of implementing the ethnic motives in the architecture of the modern restaurants’ interiors were identified, namely traditions, syncretic, ecology, flexibility, versatility, individuality, uniqueness. There was formed an algorithm of the ethnic motifs application into architectural interior design in modern catering industry.
Этнические мотивы в архитектуре современных интерьеров предприятий питания
Ethnic motives in the architecture of modern interiors of catering industry
Keywords: архітектура сучасних інтер’єрів; підприємства харчування; приміщення для відвідувачів; етнічні мотиви; архітектурно-художні засоби; методи та принципи використання етнічних мотивів; архитектура современных интерьеров; предприятия питания; помещения для посетителей; этнические мотивы; архитектурно-художественные средства; методы и принципы использования этнических мотивов; architecture of modern interiors; catering industry; facility for visitors; ethnic motives; architectural and artistic tools; methods and principles of using the ethnic motives